#TITLE_ALTERNATIVE# - Kurniawan (NIM 123 02 017), Muhammad
Abstract: AVO analysis (Amplitude Variation with Offset) is a method used to predict hydrocarbon accumulation, especially gas within sandstone. This method is not used to apply for carbonate because the behaviour of carbonate is very differing from sandstone, especially the physical character for gas saturation which is very sensitive to AVO response. Carbonate built-up character in Azzurri field can be perceived using AVO method, but it can not give the significantly anomaly of gas. This matter because of carbonate reservoir has intercrystalline porosity type, so the fluid accumulation can influences P wave velocity passing it, but P wave tends to pass the compact matrix which cause the poissons ratio is not sensitive enough to predict the fluid accumulation. Goodway proposed a new approach to AVO inversion based on the Lame parameters land and density or Lambda-Mu-Rho (LMR). The reflectivity section showing Lambda parameter and Mu contrast will be able to differentiate between litology and fluid reservoir optimally. In this case, reflectivity section of parameter contrast of Mu-Rho can be used as litology indicator. Reflectivity interpretation of Lambda-Rho section can predict fluid indicator, in this case gas.